ANALISIS SOAL DALAM BUKU MATEMATIKA KELAS VII SEMESTER 1 BERDASARKAN KRITERIA DARI HIGHER ORDER THINKING SKILLS (HOTS) - Muhammad Fauzan Darus; Adi Ihsan Imami; Agung Prasetyo Abadi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This article is the result of a study which aims to describe the HOTS content of the mathematics textbook for grade VII SMP. This research uses a qualitative approach with the type of content analysis. The subjects in this study were examples of questions and practice questions in the Mathematics textbook for Class VII of the 2013 Curriculum, the fourth revised edition of 2017 published by the Center for Curriculum and Books of the Balitbang Ministry of Education and Culture of the Republic of Indonesia. The data technique used in this research were careful reading and recording of the books under study. The data analysis techniques in this study were carried out quantitatively and qualitatively. Qualitative descriptive analysis was used to determine the percentage of HOTS in textbooks, while qualitative descriptive analysis was used to provide an overview and explanation regarding HOTS questions that will be presented.The HOTS charge results that appear in the sample questions section are 4% with indicators that appear, namely analyzing (C4) 100%, evaluating (C5) 0%, and creating (C6) 0%. Then, the HOTS load results that appear in the exercise section of this questions are 22% with indicators that appear, namely analyzing (C4) 83%, evaluating (C5) 6%, and creating (C6) 11%. Based on the results of this study, it can be concluded that HOTS content in mathematics textbooks for grade VII SMP dominates the analyzing indicator (C4) compared to other indicators.